IMOBILISASI LIMBAH RADIOAKTIF MENGANDUNG THORIUM MENGGUNAKAN BAHAN MATRIKS SYNROC - Hasmaniar Septiani; Gunandjar Gunandjar; Mochtar Hadiwidodo (Departemen Teknik Lingkungan Fakultas Teknik Universitas Diponegoro, 2013)
Thorium waste generated from mantles factories in the form of sludge with a high water content that is derived from thorium-contaminated soil. This waste includes low activity radioactive waste of long-life alpha emitter that is harmful to humans and the environment. Based on these conditions, the immobilization process is required to confine the content of thorium. This research will develop thorium waste volume reduction by adsorption process using H-Zeolite made from Zeolite of Lampung and imobilization process using synroc matrix material. This research emphasized the immobilization process to obtain waste synroc block with the best quality by studying the effect of sintering temperature and sintering time as well as the effect of waste loading in the formation process of waste synroc block. The optimum condition is achieved at the waste loading 50% with the sintering temperature of 1250 ˚ C for 3 hours.